The Influence of the Indonesia Ulema Council’s Fatwa on Cryptocurrency on the Use of Cryptocurrency by the Millennial Muslim Generation - Ulpah, Siti Nurul; Susilawati, Cucu (Universitas Siliwangi, 2025)
Introduction to The Problem: The Millennial Muslim Generation is unique, daring to try something new and cryptocurrency. Data shows that the millennial generation is the generation that uses cryptocurrency the most.Purpose/Objective Study: This study aimed to determine the influence of the Indonesian Ulema Council Fatwa on cryptocurrency and the use of cryptocurrency by the millennial Muslim generation. Design/Methodology/Approach: This study uses a quantitative approach with a descriptive method. Data collection techniques were carried out through online questionnaires of 100 respondents.Findings: The results of the study showed that the Indonesian Ulema Council Fatwa and Cryptocurrency simultaneously influenced the use of cryptocurrency by the Millennial Muslim Generation. So, it can be concluded that the substance of the Ulema Council Fatwa on Cryptocurrency is a consideration for the Millennial Muslim Generation in cryptocurrency transactions. Therefore, the substance of the Indonesian Ulema Council Fatwa does not prohibit and allow it ultimately, so the Millennial Muslim Generation needs to be careful in conducting cryptocurrency transactions that are by sharia.PapEr Type: Research Article